Pedagogical control over stabilometric indicators in ski jumping and Nordic Combined - Zebzeev, V. V.; Zdanovich, O. S.; Barinov, M. V.; Zharushkina, E. K. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to develop stabilometric group benchmarks for application at every progress stage in the modern ski jumping and Nordic combined long-term athletic training systems.